2020
DOI: 10.3390/w12020544
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative PCR Detection of Enteric Viruses in Wastewater and Environmental Water Sources by the Lisbon Municipality: A Case Study

Abstract: Current regulations and legislation require critical revision to determine safety for alternative water sources and water reuse as part of the solution to global water crisis. In order to fulfill those demands, Lisbon municipality decided to start water reuse as part of a sustainable hydric resources management, and there was a need to confirm safety and safeguard for public health for its use in this context. For this purpose, a study was designed that included a total of 88 samples collected from drinking, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 76 publications
3
22
1
2
Order By: Relevance
“…HAV RNA, not detected in the present study in surface waters, was detected in Peri Lagoon in Brazil [58] at relatively high concentrations (1.1 × 10 2 to 4.3 × 10 3 gc/L). In Portugal, Teixeira et al (2020) [44] did not detect viruses in superficial water intended for drinking water production, but Salvador et al (2020) [48] reported, for surface water samples included in this study (from the river and the dam reservoir), the detection of hepatitis E virus (HEV), which is an enteric virus not included in the present study.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…HAV RNA, not detected in the present study in surface waters, was detected in Peri Lagoon in Brazil [58] at relatively high concentrations (1.1 × 10 2 to 4.3 × 10 3 gc/L). In Portugal, Teixeira et al (2020) [44] did not detect viruses in superficial water intended for drinking water production, but Salvador et al (2020) [48] reported, for surface water samples included in this study (from the river and the dam reservoir), the detection of hepatitis E virus (HEV), which is an enteric virus not included in the present study.…”
Section: Discussionmentioning
confidence: 77%
“…The microbial indicators of fecal contamination included in that list are fecal indicator bacteria (FIB), comprising coliform bacteria (Escherichia coli and other coliforms), and intestinal enterococci [42]. Although FIB have been considered effective indicators of the presence of other pathogens, this association has been questioned [43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteriophage PP7 was utilized by Fumian et al (2010) as a process control to determine the efficiency of concentration of RoV-A from wastewater samples. Mengovirus strain vMC0 has been used as a process control virus to assess the efficiency of concentration, nucleic acid extraction, and detection of enteric viruses from water samples ( Coudray-Meunier et al, 2015 ; Teixeira et al, 2020 ). Farkas et al (2018) utilized mengovirus strain vMC0 as a process control to assess the efficiency of different concentration methods in the recovery of enteric viruses from wastewater samples.…”
Section: Detection Methods Of Viruses In Wastewatermentioning
confidence: 99%
“…Inconsistency was most often observed due to inhibitory substances present in a stool sample (bile salts, polysaccharides, lipids, and urate) and other samples (debris, humic acids, and polyphenols) as they co-precipitates or adsorbs with nucleic acid during the detection [143] . Cloning, metagenomic analysis (virus), and RT-qPCR with the use of process controls help to detect viruses accurately by knowing the virus recovery rate and the level of inhibition [121] , [144] , [145] , [146] , [147] . The selectivity and choice of process controls depend on the molecular and biochemical structure of the virus and their route of infection [148] , [149] .…”
Section: Detection Of Virus In Environmental Matricesmentioning
confidence: 99%